PERAN IBU DALAM MEMENUHI KEBUTUHAN GIZI SEIMBANG BATITA DI DUSUN BUNGKEM DESA KWEDEN KEMBAR KECAMATAN MOJOANYAR KABUPATEN MOJOKERTO - Indatul Laili, Siti; Wulandari, Yani (JURNAL KEPERAWATAN SEHAT, 2015)
The golden age was a time of growth and development at this age is a period of rapid and never repeated, which of children age 1 – 3 years should be given food with balanced nutrition. So that mothers play an important role in providing balanced nutrition for toddlers. The purpose of this research was to determine the role of the mother in meeting the nutritional needding of toddlers in Bungkem village, Kweden Kembar, Mojoanyar, Mojokerto district. The research design used descriptive. The sampel was all of people who hade decision criteria for inclusion with purposive sampling teckhnic. The data was taken by a questionnaire cantaining 20 question. Research result was 11 people (55%) with a negative role in education because of poor factor. Good mothers who have little education are well educated in the expected increase understanding or searching for information about nutritional requirements needed by toodlers throught counseling at the time of early childhood facilities in the local authorities so as to address the role of the mother is negative and can improve child nutrition.Keywords: Roles, Toodlers, Nutritional needs.